HARRY POTTER'S AMBITION IN J.K ROWLING'S HARRY POTTER AND THE CHAMBER OF SECRETS: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - WIDYANINGSIH, AMALIA (2006)
The problem statement of this study is how Harry's ambition influences her personality in Rowling's the Chamber of Secret. There are two objectives of the study. The first the researcher tries to analyze the factors that influence Harry in reaching her ambition by applying Alfred Adler's theory of individual psychology. The second objective is to analyze the structural elements of the play. The object of research paper is the play entitled the Chamber of Secret. This study belongs to qualitative study. In this method the researcher uses two data sources: primary data and secondary data. The primary data is novel, mean while the secondary data dealing with J.K Rowling's work and other sources based on movie version of Harry Potter and the Chamber of Secrets. The technique of data analysis in this study is descriptive and comparative technique. The results of the study show that some aspects of individual psychology influence ambition and the theme of Rowling's Harry Potter and the Chamber of Secrets.